Petrogenesis of the Gualcamayo Igneous Complex: Regional implications of Miocene magmatism in the Precordillera over the Pampean flat-slab segment, Argentina - D'annunzio, María Celeste (2018)
The Gualcamayo Igneous Complex is located over the Pampean flat-slab segment (28–33°S), ∼110 km eastward from the Upper Miocene front arc position. It consists of subvolcanic rocks that are affected by porphyry-type hydrothermal alteration, and are genetically linked to a cluster of Carlin-type, skarn and epithermal gold deposits at the Gualcamayo mining district. The petrogenetic analysis of these volcanic rocks allows suggesting that this late Miocene (∼9 Ma) arc-related magmatism with an adakitic signature derives from asthenospheric mantle magmas that under thickened crust conditions, evolved through amphibole fractionation with lower crust melting, probably involving Grenvillian amphibolites from the basement of the Precordillera. These melts evolved towards shallower magma chambers, where they fractionated amphibole and plagioclase, leading to a variable adakitic signal.